Cellulose and chitosan chloride hydrogels applied in tissue engineering - Ono, Bruno Andrade (2022)
The present study researches a low-cost membrane of cellulose and chloride chitosan for cell growth. This material was used as cells support without growth factors and using only the physical and molecular properties interactions to promote cells adhesion and development. The quaternized chitosan derivative was synthetized with two different molecular properties: linear density of positive charge and molecular weight. The interaction of cellulose and these synthetized chitosan lead to four different hydrogels through the combination of these properties. Firstly, the molecules of chitosan were synthetized and characterized by different biophysics techniques as RMN and FT-IR. Secondly, the material was also characterized to understand the interaction between cellulose and chitosan derivates molecules to develop the membrane with the help of confocal microscopy. Lastly, the interaction of these membranes with human cells (MG63) and bacteria (E. coli) was tested to observe the biological response to this new support. The results of synthesis indicate a chitosan derivative with 8% to 40% of positive linear density and a molecular weight around 400 and 900 kg/mol. The higher cell attachment (near to 60%), low cytotoxicity and high cell spreading was observed for the higher DQ similar to the tissue culture plate. The gram-negative bacteria (E. coli) had the biggest damage at higher DQ membranes, however the same material presented the higher number of E. coli attach to it. These results present a low-cost natural source of biomolecules which have nowadays high technologic impact and could be used for developing a potential membrane for tissue engineering. This study was only possible through national and international collaboration with researchers from the University of Bath and the São Carlos Institute of Chemistry.